PENGARUH KOMPRES HANGAT TERHADAP MOTILITAS USUS PADA PASIEN APENDIKTOMI - WIranata, Ardy (Coping: Community of Publishing in Nursing; Vol 2 No 2 (2014): JURNAL EDISI MEI-AGUSTUS 2014, 2014)
1024x768 Appendectomy is a medical operation to remove the appendix and it must be done as soon as possible to reduce the risk of perforation. Most patients after the surgery decreased intestinal motility because of the direct manipulation and anesthesia during the surgery. One of the fastest recoveries for intestinal motility can be done thrash applying the warm compress on the left abdomen of the patients. The purpose of this research was to find out the impact of warm compresses on intestinal motility of the appendectomy patient at Bougenville room, BRSU Tabanan. This research used nonequivalent control group design with 24 people who are divided into 2 groups; they are control group and intervention group. Intestinal motility value can be obtained from the examination in all four quadrants of the abdomen using a stethoscope. Data were analysed useing t-test independent is p< ? (p = 0,000; ? = 0.05) Which has a significant impact of warm compress on intestinal motility among appendectomy patients. Based on the result of the research, it is suggested that the appendectomy patients should have warm compress toincrease intestinal motility. Hence Length of Stay patient will shorter. Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Warm Compress, Intestinal Motility, Appendictomy